Morphosyntactic Skills Influence the Written Decoding Accuracy of Italian Children With and Without Developmental Dyslexia - Casani, Emanuele; Vulchanova, Mila; Cardinaletti, Anna (Frontiers in Psychology, 2022)
Some types of Developmental Dyslexia (DD) are associated with morphology. Deep DD leads to morphological and semantic errors, and possible comorbidity with syntactic deficits; phonological-output-buffer DD causes problems in decoding longer morphologically complex words. In addition, cross-linguistic studies highlight the effects of morphological awareness on reading accuracy and fluency. The role of morphosyntactic abilities on reading is however not clear. This study explores the influence of morphosyntactic competence on reading in Italian children with and without DD. Fourteen children with DD and twenty-eight with Typical Development (TD) attending the Italian primary school were tested on written decoding, syntactic comprehension of different grammatical structures, and syntactic production of direct object clitic pronouns. DD-children were significantly less accurate and slower in reading than TD children. Syntactic skills of the two groups did not differ significantly, but some differences in their acquisitional pace emerged. Syntactic comprehension and production of direct-object-clitic pronouns predicted reading accuracy standard scores, thus suggesting that morphosyntactic abilities, beyond clitics’ weak phonological status, affect decoding accuracy. Decoding accuracy was influenced by reading errors related to morphology (morphological, semantic, and phonological-output-buffer errors). Decoding speed was a specific weakness of DD children and was rather affected by multi-letter combinations. Consistent with a dual-route approach to orthographic processing, we argue that accuracy depends on fine-grained decoding strategies maximizing the precise ordering of letters, thus it is more sensitive to morphosyntactic skills. Morphological reading errors were associated with phonologically weak (determiners, clitic pronouns, prepositions) and salient words (verbs). This suggests that the decoding of function words and morphologically complex words is particularly demanding and related to both phonological and morphosyntactic skills. Age had a negative predictive effect on semantic errors, compatible with the gradual acquisition of lexical decoding strategies, which seemed to be slowed down by DD. We conclude that oral morphosyntactic skills play a role in reading accuracy in the Italian shallow orthography for both DD and TD children. It is then advisable to assess children’s linguistic profile during DD diagnoses to establish whether some reading errors are related to morphosyntactic weakness. In this case, ad hoc morphosyntactic training might support reading accuracy.